To Make Negro Literature Writing, Literary Practice, and African American Authorship - McHenry, Elizabeth (Duke University Press, 2021)
Elizabeth McHenry locates a hidden chapter in the history of Black literature at the turn of the twentieth century, revising concepts of Black authorship and offering a fresh account of the development of "Negro literature" focused on the never published, the barely read, and the unconventional.